2016
DOI: 10.1136/vetreccr-2015-000271
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body‐induced meningoencephalitis causing seizures in a dog

Abstract: A young Magyar vizsla dog was presented with seizures and progressive neurological deterioration in terms of symmetric prosencephalic signs despite induction of antiepileptic therapy. Cerebrospinal fluid (CSF) analysis and MRI findings were suggestive of an inflammatory process. This finding was confirmed at postmortem examination and a plant foreign body penetrating the cerebrum was found. Migrating plant material is an uncommon cause of inflammation in the CNS in dogs. It should be considered an aetiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Intracranial foreign bodies are uncommonly reported in the veterinary literature . Previous successful treatment has been reported just in one cat with no confirmation of brain parenchyma penetration .…”
Section: Discussionmentioning
confidence: 93%
“…Intracranial foreign bodies are uncommonly reported in the veterinary literature . Previous successful treatment has been reported just in one cat with no confirmation of brain parenchyma penetration .…”
Section: Discussionmentioning
confidence: 93%
“…Within the veterinary literature, few papers describe intracranial migration of foreign material through obscure routes (Dennis et al 2005, Lazzerini et al 2016. McKenzie et al (2019) and Sauvé et al (2012), identified a wooden cocktail stick and a porcupine quill crossing the foramen ovale; Caraty et al (2020) detected a needle perforating the caudal cranial fossa.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, intracranial foreign bodies have been described as a consequence of perforations through the oral cavity, the nasal cavity and the orbits (Daoust 1991, Dennis et al 2005, Sauvé et al 2012, Lazzerini et al 2016, McKenzie et al 2019, Caraty et al 2020. This case report describes a sewing needle swallowed by a dog that passed into the right neurocranium through the right foramen lacerum.…”
Section: Introductionmentioning
confidence: 97%
“…14 In a case report, a young Hungarian Vizsla had a seizure and progressive neurological deterioration. 15 The MRI showed diffuse intra-axial T2W and fluid attenuated inversion recovery hyperintensity throughout the right cerebral hemisphere, and a mass effect with midline shift to left was seen. After the MRI, the dog did not regain spontaneous breathing and euthanasia was chosen.…”
Section:  Of mentioning
confidence: 91%
“…All dogs were euthanased (without prior diagnostic imaging), and postmortem examination revealed a grass awn migration and severe signs of inflammation in right occipital lobe (one dog) and right lateral ventricle (another two dogs) 14 . In a case report, a young Hungarian Vizsla had a seizure and progressive neurological deterioration 15 . The MRI showed diffuse intra‐axial T2W and fluid attenuated inversion recovery hyperintensity throughout the right cerebral hemisphere, and a mass effect with midline shift to left was seen.…”
Section: Introductionmentioning
confidence: 99%